Impact of biochar on mobilization, methylation, and ethylation of mercury under dynamic redox conditions in a contaminated floodplain soil. (June 2019) - Beckers, Felix; Awad, Yasser Mahmoud; Beiyuan, Jingzi; Abrigata, Jens; Mothes, Sibylle; Tsang, Daniel C.W.; Ok, Yong Sik; Rinklebe, Jörg
Abstract: Mercury (Hg) is a highly toxic element, which is frequently enriched in flooded soils due to its anthropogenic release. The mobilization of Hg and its species is of ultimate importance since it controls the transfer into the groundwater and plants and finally ends in the food chain, which has large implications on human health. Therefore, the remediation of those contaminated sites is an urgent need to protect humans and the environment. Often, the stabilization of Hg using amendments is a reliable option and biochar is considered a candidate to fulfill this purpose. We tested two different pine cone biochars pyrolyzed at 200 °C or 500 °C, respectively, with a view to decrease the mobilization of total Hg (Hgt ), methylmercury (MeHg), and ethylmercury (EtHg) and/or the formation of MeHg and EtHg in a contaminated floodplain soil (Hgt : 41 mg/kg). We used a highly sophisticated automated biogeochemical microcosm setup to systematically alter the redox conditions from −150 to 300 mV. We continuously monitored the redox potential (EH ) along with pH and determined dissolved organic carbon (DOC), SUVA254, chloride (Cl − ), sulfate (SO4 2− ), iron (Fe), and manganese (Mn) to be able to explain the mobilization of Hg and its species. However, the impact of biochar addition on Hg mobilization was limited. We did not observe a significant decrease of Hgt, MeHg, and EtHg concentrations after treating the soil with the different biochars, presumably because potential binding sites for Hg were occupied by other ions and/or blocked by biofilm. Solubilization of Hg bound to DOC upon flooding of the soils might have occurred which could be an indirect impact of EH on Hg mobilization. Nevertheless, Hgt, MeHg, and EtHg in the slurry fluctuated between 0.9 and 52.0 μg/l, 11.1 to 406.0 ng/l, and 2.3 to 20.8 ng/l, respectively, under dynamic redox conditions. Total Hg concentrations were inversely related to the EH ; however, ethylation of Hg was favored at an EH around 0 mV while methylation was enhanced between −50 and 100 mV. Phospholipid fatty acid profiles suggest that sulfate-reducing bacteria may have been the principal methylators in our experiment. In future, various biochars should be tested to evaluate their potential in decreasing the mobilization of Hg and to impede the formation of MeHg and EtHg under dynamic redox conditions in frequently flooded soils. Graphical abstract: Unlabelled Image Highlights: Biochars had little influence on total Hg (Hgt ) release, methylation, & ethylation. Biochars likely curtailed Hgt release at redox potential (EH ) around −110 mV. Concentrations of EtHg and MeHg were highest at EH s 0 mV and 100 mV, respectively. Phospholipid fatty acid profiles suggest sulfate-reducing bacteria as methylators.